Entrepreneurship and Human Capital in Professional Sport: A Longitudinal Analysis of the Italian Soccer League. (January 2018) - Radaelli, Giovanni; Dell'Era, Claudio; Frattini, Federico; Messeni Petruzzelli, Antonio
The discovery and deployment of human capital are overlooked topics in entrepreneurship research. Professional sport can illuminate these phenomena as sport directors take huge risks in innovating rosters. Our longitudinal analysis of the Italian Serie A investigated if sport directors with greater entrepreneurial orientations toward the acquisition of new players outperformed rivals. While soccer organizations with better roster quality and accomplished managers achieved superior rankings, the acquisition of new players had nonsignificant effects and was moderated negatively by accomplished managers. We argue that entrepreneurs risk with "too many" talents while conformity mechanisms attenuate the entrepreneurial opportunities offered by human capital.